Dissociating social reward learning and behavior in alcohol use disorder - Simon Jangard; Björn Lindström; Lotfi Khemiri; Nitya Jayaram-Lindström; Andreas Olsson (Translational Psychiatry)
Abstract Background Alcohol use disorder (AUD) is associated with deficits in social cognition and behavior, but why these deficits are acquired is unknown. We hypothesized that a reduced association between actions and outcomes for others, i.e., social reward learning, would explain prevalent social deficiencies in AUD. Methods We conducted one laboratory study (n = 234) and one confirmatory online study (n = 258), comparing young adults with AUD to age-, gender-, and education-matched healthy controls on a standardized reward learning task. In the task, participants learned to maximize reward for another person and for oneself. To elucidate the potential relation between reward learning and social behavior in AUD, we administered two measures: a dictator game task and a self-report measure. Finally, we applied reinforcement learning models to examine the computational properties of learning. Results Social and individual learning, expressed in choice behavior, were comparable in individuals with AUD and healthy controls. Individual differences in learning were not associated with reduced social behavior in AUD. Computational modeling suggested that the learning mechanisms are comparable in AUD and healthy controls and indifferent to whether learning maximizes reward for another person or oneself. Conclusions Individuals with AUD demonstrated preserved reward learning abilities that do not vary with social behavior. Together, these results indicate that reward processes may not be relevant for understanding compromised social behavior in AUD.